Passion or perseverance? The eﬀect of perceived autonomy support and grit on academic performance in college students - Hernández, Elisa Huéscar (2020)
Background: Individuals who possess passion and perseverance to extensively work and studythroughchallengesandadversitytoachieveasetofgoalsarelikelytoreachhigherachievement compared to others who lack similar facets. However, an under-researched question lingers over the eﬀect of teacher-induced behaviors on academic outcomes such as grades and performance. The purpose of this study was to examine the relationships between teacher-induced autonomy support and student academic performance considering the mediating eﬀect of basic psychological needssatisfaction,intrinsicmotivation,andgritastwo-independentfactors. Methods: Aconvenience sample of 474 Sports Science students (Mage = 21.83 years; SD = 3.91) participated in the study. All participants completed a multi-section survey assessing the variables under analysis. Results: Themeasurementandstructuralmodeldisplayedacceptableﬁt,hencedirectandindirecteﬀectswere examinedamongthevariablesofinterest. Basicpsychologicalneedsandintrinsicmotivationseemto display a mediating role between perceived autonomy support and academic performance, through perseverance. Contrarily, grit-passion did not exhibit a signiﬁcant indirect eﬀect. Conclusions: Current results shed new insights on how perseverance can shape student motivation and school success considering the autonomy support induced by teachers.